[HSO3-pmim][CH3SO3] Catalyzed One-Pot Protocol for the Synthesis of Coumarins Under Solvent-Free Conditions - Song, S.J.; Liu, W.H.; Ma, J.J.; Qi, J.M. (Asian Journal of Chemistry, 2012)
A mild and efficient protocol for the synthesis of coumarins from different phenol and ethyl acetoacetate via Pechmann reacation using acidic ionic liquids [1-methyl-3-(3-sulfopropyl)- imidazolium methyl sulphate] as catalyst under solvent-free conditions has been developed. The advantages of this protocol are low catalyst loading, better yields, shorter reaction time and environmentally benign.